First records of the druid fly genus Clusia Haliday, 1838 (Diptera, Clusiidae), with two new species from China - Shen, Shuang; Zhu, Yongqiang; Liu, Chang; Yang, Ding; Xi, Yuqiang (Zootaxa, 2023)
The druid fly genus Clusia was firstly recorded from China, including two new species: C. luteimacula sp. nov. from Yintiaoling Nature Reserve of Chongqing and C. sinensis sp. nov. from Wanglang of Sichuan and Mt. Taibai of Shaanxi. A key to all species of Clusia globally is presented.